EVALUATION OF TRICHODERMA HARZIANUM AND PSEUDOMONAS FLUORESCENS ISOLATES FOR THEIR ANTAGONISTIC POTENTIAL AGAINST EXSEROHILUM TURCICUM CAUSING LEAF BLIGHT OF SORGHUM - VAIBHAV SINGH; YOGENDRA SINGH (The Bioscan, 2014)
Antagonist potential of seventeen isolates of Trichoderma harzianum and ten isolates of Pseudomonas fluorescens was determined against Exserohilum turcicum in vitro using dual culture technique. Th-39 and Psf- 82 gave maximum inhibition of mycelial growth of the pathogen by 77.11 and 56.00 percent respectively. Th-39 and Psf- 82 isolates proved their worthiness in glasshouse as well as field conditions also reducing the maximum disease severity by 58.64% and 50.00% (glasshouse) and 35.59% and 30.30% (field) respectively using three sprays. Considering the biocontrol potential of these agents in disease suppression they can be recommended for disease management.